The Moderating Role of Environmental Factors in the effect of Scenario Planning On Future Foresight : Case study of the Ministry of Digital Economy and Entrepreneurship in Jordan - M.S. Idris, Wael; M. ALgalibi, Taher; M. ALshebli, Hussein (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to investigate the Moderating Role of Environmental Factors( Environmental Dynamism and Environmental Complexity ) in the effect of Scenario Planning dimensionson Future Foresight dimensions in Minister of Digital Economy and Entrepreneurship at Jordan.The study population consisted of all workers in Minister of Digital Economy and Entrepreneurship at Jordan, While the study dample included the departments directors,their deputies ,their assistants and section heads working in the Minister of Digital Economy and Enterpreneurship at Jordan or their repesentatives totaling (56)individuals who were purposive selected . To achieve the study objectives , the descriptive method was used in presenting data and the analytical approach in analyzing it's results through the questionnaire .The researchers resorted to the SPSS program, the twenty-fourth edition ,through which hierarchical regression analysis was used. The study found thatenvironmental factors (environmental dynamics and environmental complexity) Play a moderate role in the effect of scenario planning dimensions on Future Foresight dimensions in Minister of Digital Economy and Entrepreneurship at Jordan. The study recommended the Minister of Digital Economy and Entrepreneurship at Jordan need to benefit from the scenario planning approachs of their reflections in environmental factors in integration with future foresight techniques, by preparing an integrated study to clarify the utilization levels of scenario planning approachs and future foresight techniques.